2007
DOI: 10.1007/s11627-007-9050-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel Agrobacterium rhizogenes-mediated transformation method of soybean [Glycine max (L.) Merrill] using primary-node explants from seedlings

Abstract: A novel Agrobacterium rhizogenes-mediated transformation method using a primary-node explant from Dairyland cultivar 93061 was developed for soybean using the disarmed Agrobacterium strain SHA17. Transformed plants regenerated from explants inoculated with SHA17 were fertile and phenotypically normal. In a comparative experiment, regeneration frequencies were not significantly different between explants inoculated with A. rhizogenes strain SHA17 and Agrobacterium tumefaciens strain AGL1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Regeneration through organogenesis was successfully obtained using cotyledonary nodes (Paz et al 2006), primary leaves (Wright et al 1987), shoot meristems (McCabe et al 1988) and mature seed-derived embryonic tips (Liu et al 2004). Though genetic transformation and subsequent plant regeneration via organogenesis is well established in this valuable crop (Liu et al 2004;Paz et al 2006;Hong et al 2007;Olhoft et al 2007), somatic embryogenesis is still highly preferred over organogenesis, as the transformants derived through embryogenesis are more uniform and the chances for the occurrence of variation among individual clones are lesser (Terzi and Lo Schiavo 1990;Osuga et al 1999). Furthermore, regeneration through somatic embryogenesis has certain advantages: (1) it is an efficient and high volume propagation system, hence less labour intensive, and (2) the embryogenic cultures developed from this system are pure and homogeneous, owing to their single cell origin (Jiménez 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Regeneration through organogenesis was successfully obtained using cotyledonary nodes (Paz et al 2006), primary leaves (Wright et al 1987), shoot meristems (McCabe et al 1988) and mature seed-derived embryonic tips (Liu et al 2004). Though genetic transformation and subsequent plant regeneration via organogenesis is well established in this valuable crop (Liu et al 2004;Paz et al 2006;Hong et al 2007;Olhoft et al 2007), somatic embryogenesis is still highly preferred over organogenesis, as the transformants derived through embryogenesis are more uniform and the chances for the occurrence of variation among individual clones are lesser (Terzi and Lo Schiavo 1990;Osuga et al 1999). Furthermore, regeneration through somatic embryogenesis has certain advantages: (1) it is an efficient and high volume propagation system, hence less labour intensive, and (2) the embryogenic cultures developed from this system are pure and homogeneous, owing to their single cell origin (Jiménez 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies reported that soybean cultivars vary in there susceptibility to infection by armed A. tumefaciens and A. rhizogenes strains (Owens and Cress 1985;Byrne et al 1987;Savka et al 1990). In our companion paper (Olhoft et al 2007), we presented data that shows SHA17-inoculated explants had an average transformation efficiency of 6.8% vs. 1.85% from AGL1-inoculated explants using a novel transformation method that targets the primary node's axillary meristem cells for T-DNA delivery. Of the A. rhizogenes strains tested in soybean, the strain K599 induced the highest frequency of hairy root development from a wide range of genotypes tested (Savka et al 1990;Cho et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Sterile soybean primary node explants were transiently and stably transformed according to Olhoft et al (2007) with Agrobacterium strains AGL1 (Lazo et al 1991) and SHA17 harboring the binary vector pBPSEW008 (Fig. 5i).…”
Section: Methodsmentioning
confidence: 99%
“…A combined use of the genomic data, germplasms resources, and unique genetic populations will open up new ways to identify functional genes related to osmotic stress tolerance. The low efficiency of soybean transformation (by Agrobacterium-mediated or biolistics approaches (Olhoft et al, 2007;Rech et al, 2008) remains a major obstacle in functional tests, despite the vast success in the production of transgenic soybean globally. There is a urgent need for the soybean researchers to optimize the transformation system or to explore alternatives, including the use of the soybean hairy root transformation system (Cao et al, 2009), the ovary-drip transformation system (Liu et al, 2009a), and the transformation systems of other legumes such as alfalfa (Zhang et al) and Lotus japonicus (Aoki et al, 2002;Lombari et al, 2003).…”
Section: Future Perspectivesmentioning
confidence: 99%